Effects of total sleep deprivation on endurance cycling performance and heart rate indices used for monitoring athlete readiness - Roberts, S. S. H.; Teo, W.-P.; Aisbett, B.; Warmington, S. A. (Journal of Sports Sciences, 2019)
This study investigated effects of total sleep deprivation on self-paced endurance performance, and heart rate (HR) indices of athletes' "readiness to perform". Endurance athletes (n = 13) completed a crossover experiment comprising a normal sleep (NS) and sleep deprivation (SD) condition. Each required completion of an endurance time-trial (TT) on consecutive days (D1, D2) separated by normal sleep or total sleep deprivation. Finishing time, perceived exertion (RPE), mood, psychomotor vigilance (PVT), and HR responses were assessed. Time on D2 of SD was 10% slower than D2 of NS (64 ± 7 vs 59 ± 4 min, P < 0.01), and 11% slower than D1 of SD (58 ± 5 min, P < 0.01). Subjective to objective (RPE:mean HR) intensity ratio was higher on D2 of SD compared with D2 of NS and D1 of SD (P < 0.01). Mood disturbance and PVT mean response time increased on D2 of SD compared with D2 of NS and D1 of SD. Anaerobic threshold and change in TT time were correlated (R = -0.73, P < 0.01). Sleep helps to optimise endurance performance. Subjective to objective intensity ratios appear sensitive to effects of sleep on athletes` readiness. Research examining more subtle sleep manipulation is required.